Using l‐Carnitine as a Pharmacologic Probe of the Interpatient and Metabolic Variability of Sepsis. Issue 9 (10th August 2020) - Jennaro, Theodore S.; Puskarich, Michael A.; McCann, Marc R.; Gillies, Christopher E.; Pai, Manjunath P.; Karnovsky, Alla; Evans, Charles R.; Jones, Alan E.; Stringer, Kathleen A.
Abstract : Objective: The objective of this review is to discuss the therapeutic use and differential treatment response to Levo‐carnitine (l ‐carnitine) treatment in septic shock, and to demonstrate common lessons learned that are important to the advancement of precision medicine approaches to sepsis. We propose that significant interpatient variability in the metabolic response to l ‐carnitine and clinical outcomes can be used to elucidate the mechanistic underpinnings that contribute to sepsis heterogeneity. Methods: A narrative review was conducted that focused on explaining interpatient variability in l ‐carnitine treatment response. Relevant biological and patient‐level characteristics considered include genetic, metabolic, and morphomic phenotypes; potential drug interactions; and pharmacokinetics (PKs). Main Results: Despite promising results in a phase I study, a recent phase II clinical trial of l ‐carnitine treatment in septic shock showed a nonsignificant reduction in mortality. However, l ‐carnitine treatment induces significant interpatient variability in l ‐carnitine and acylcarnitine concentrations over time. In particular, administration of l ‐carnitine induces a broad, dynamic range of serum concentrations and measured peak concentrations are associated with mortality. Applied systems pharmacology may explain variability in drug responsiveness by using patient characteristics to identify pretreatment phenotypes most likely to derive benefit from l ‐carnitine. Moreover, provocation of sepsis metabolism with l ‐carnitine offers a unique opportunity to identify metabolic response signatures associated with patient outcomes. These approaches can unmask latent metabolic pathways deranged in the sepsis syndrome and offer insight into the pathophysiology, progression, and heterogeneity of the disease. Conclusions: The compiled evidence suggests there are several potential explanations for the variability in carnitine concentrations and clinical response to l ‐carnitine in septic shock. These serve as important confounders that should be considered in interpretation of l ‐carnitine clinical studies and broadly holds lessons for future clinical trial design in sepsis. Consideration of these factors is needed if precision medicine in sepsis is to be achieved.